Critical Analysis of Ex Post Facto Environmental Impact Assessment Authorisations in South African Law - Ndlovu, Sibonelo (Institute of Marine and Environmental Law, 2014)
In this dissertation I consider the issue of ex post facto EIA authorisations from the inception of the EIA regime in South African law to present. At the heart of the analysis is the question of whether, at different stages of the evolvement of the EIA regime, such authorisations are provided for in South African law, adequately or at all.